La gestión de la calidad del servicio y la satisfacción del cliente en el taller multimarca Burgos Motor´s - Pérez Rivera, Juan Fernando (2024)
ABSTRACT: This research is aimed to determine the management of service quality and its impact on customer satisfaction at Burgos Motor's multi-brand workshop in response to the main problem, a lack of customer service management, repair processes, and vehicle preparation. It is necessary to point out that the research work has a qualitative-quantitative, descriptive, explanatory, documentary, correlative, and field approach. The population analyzed consisted of external customers who make up the portfolio of frequent customers, with a sample number of 149 people, to whom a survey and direct observation were applied, where the processing of statistical data using Cronbach's Alpha made the study tool viable. At the same time, the hypothesis was tested using Spearman's Rho correlation, which determined the degree of influence between the independent variable "Service quality management" and the dependent variable "Customer satisfaction." Consequently, the management of service quality and its impact on customer satisfaction was analyzed using the Servqual model in Burgos Motor's multi-brand workshop. As a result of the research, a management model was designed through a Strategic Plan for the Multi-brand Workshop "Burgos Motors." This tool will allow improving expectations, quality management, and customer satisfaction.